Limites e dissonâncias da razão comunicativa: uma crítica a partir do Problema da estética - Arthur Eduardo Grupillo Chagas (2012)
The critique of reason is as old as herself, because reason is just that: the ability to put things on hold, to snatch away from them the obviousness, and to require them to plea, as required of an owner your title. Around the middle of the twentieth century, this criticism seems to have exhausted the possbilities of renewal, what stimulated thinkers such as Jürgen Habermas to formulate a broadened or enriched concept of reason, which would essentially have two advantages over the outdated model. The first one concerns the aptitude of this renewed figure of reason to include the other of the subject-centered reason, namely the aesthetic experience. The second one focuses on how this inclusion is accomplished by an incorporation of reason into language, therefore through a linguistification of aesthetic experience. The present thesis proposes to investigate how this conceptual strategy, although justified, comes up against limits, which, striclty speaking, should notbe imputed to rationality itself. Communicative reason should therefore not be susceptible to an autophagic critique, something like a negative dialectics. However, insofar asit must take into account the cognitive potential of these limits imposed by a world-disclosing language, it internalizes dissonant normative assumptions. Since the experience with art offersthe clearest example of this potencial, while raising a specific rational claim, it has the methodological prerogative to allow a critique of communicative reason which does not become self-referential, but which has been put from a problem: the problem of aesthetics.